ANALISIS POLA PERILAKU PACARAN PADA REMAJA - Anitsnaini Sirojammuniro (Academic Journal of Psychology and Counseling, 2020)
Adolescence is a period of transition from childhood to adulthood. A prominent feature of adolescents in adolescent development is the existence of feelings to love and be loved by others. The capacity to give to one another is equally important to receive love that is generally expressed by dating. The purpose of this study is to describe adolescent courtship behavior, influencing factors, and dating behavior patterns in adolescents. The method used in this research is exploratory qualitative with a data collection tool in the form of an open questionnaire and diary monitoring.           Based on research results found that adolescent dating behavior is divided into two categories, namely dating behavior when with friends and dating behavior when together. Based on the results of the study found that dating in adolescents is still in the category of healthy dating. However, dating behavior in adolescents falls into the category of risky dating behavior. Dating status and never dating affect dating behavior. Factors that influence dating behavior in adolescents include internal factors, friend factors, family factors, and also permissive attitude factors. Adolescent dating patterns of behavior starts from the process of introduction, the process of approach, the process of fall in love, the process of expressing love, the process of going out dating, the process of problem arising, the process of problem solving, and the process of decision making for the continuation of relationships. adolescents tend to do emotion focus coping before solving problems. There are differences in problem solving between adolescent girls and boys.